Three new records of the conger eels (Anguilliformes: Congridae) from Taiwan and the Dongsha Islands - Huang, Jian-Fu; Chen, Hong-Ming; Chan, Tin-Yam (Zootaxa, 2024)
Three newly recorded species of conger eels were recently discovered in Taiwanese waters and the South China Sea. These are Heteroconger polyzona Bleeker, 1868; Parabathymyrus philippinensis Ho, Smith & Shao, 2015; and Congriscus maldivensis (Norman, 1939). A brief description of the Taiwanese collections is provided in this paper.